How To Measure Audit Quality By Considering The Factors Of Professionalism, Accountability and Auditor Independence - Asyari; Yartono, Nungki; Achyarsyah, Padri; Awaloedin, Dipa Teruna (CV ODIS, 2024)
Audit quality is measured based on audit report findings of violations in the client's accounting system. Financial reports are an important source of information for parties who need reports. Financial information is created by management to determine the company's financial condition, make decisions, and make it easier to manage the company. This research was conducted to determine the influence of auditor independence, accountability and auditor professionalism on audit quality. This research uses primary data in the form of respondents' answers to questionnaire data collection. This research used a simple random sampling method in determining the sample and there were 54 samples that met the criteria. This research uses multiple linear regression analysis and t test and R Square test for data analysis techniques. where the research results show that the variables of auditor independence, accountability and auditor professionalism simultaneously influence audit quality. Partially, auditor independence has a positive effect on audit quality, auditor accountability and auditor professionalism have a significant positive effect on audit quality